Religion and Politics under Capitalism: A Humanistic Approach to the Terminology - Arvidsson, Stefan (Routledge Studies in Religion Ser., 2019)
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- List of figures -- List of tables -- Preface -- Part I -- 1 Totalitarianism and political religion -- 2 Mythic politics and the masses -- 3 Liberalism and capitalist religion -- Part II -- 4 Secular age, idealist scholarship -- 5 "Everything religion" and the capitalist framework -- 6 A humanistic view on religion -- Part III -- 7 Basic definitions -- 8 Relating modern religions and political ideologies -- Bibliography -- Index.